2021
DOI: 10.3390/ijerph18189775
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Peer Attachment on Left-Behind Children’s Pathological Internet Use: A Moderated Mediating Effect Model

Abstract: The aim of this study was to determine how left-behind children’s perceived personal rejection and emotional intelligence impact on the relationship between their peer attachment and pathological Internet use in China. Using the cluster random sampling method, a total of 406 left-behind children (aging 12.76 ± 2.13) from six rural primary and secondary schools in mainland China were recruited for the study (202 males and 204 females). The results of the analysis indicated that peer attachment negatively predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…PTG can result in enhanced interpersonal connections, more compassion, openness, admiration for life, spiritual development, personal strength, and a revitalized sense of possibility in the world. Zhang and Wang's research [12] indicated that left-behind children whose interpersonal environment was unfavorable might nonetheless develop PTG, determined by the presence of protective variables that enabled them to withstand the harmful effects of the unfavorable environment.…”
Section: Introductionmentioning
confidence: 99%
“…PTG can result in enhanced interpersonal connections, more compassion, openness, admiration for life, spiritual development, personal strength, and a revitalized sense of possibility in the world. Zhang and Wang's research [12] indicated that left-behind children whose interpersonal environment was unfavorable might nonetheless develop PTG, determined by the presence of protective variables that enabled them to withstand the harmful effects of the unfavorable environment.…”
Section: Introductionmentioning
confidence: 99%
“…It indicates that close friendship support strongly contributes to the resilience of adolescents through the provision of social support and active engagement. Furthermore, studies of left‐behind adolescents in China and Nepal have found that school support and friendship quality are important resources for preventing psychosocial problems in left‐behind adolescents due to a lack of family support (Kharel et al, 2021; Zhang & Wang, 2021). However, our study did not find friendship quality directly reduced the risk of later depressive and anxious symptoms but could reduce it by enhancing resilience.…”
Section: Discussionmentioning
confidence: 99%
“…A longitudinal study conducted by Wartberg et al (8) found that male sex, severe self-esteem problems, and severe hyperactivity symptoms are predictors of problematic online gaming behavior. In addition to the above, several other studies focusing on risk factors for IGD support that many variables are significantly associated with the development of IGD, including video game cost (9,10), gaming time (11,12), difficulty in emotion regulation (13), higher impulsivity (11,14,15), hyperactivity symptoms (16)(17)(18)(19), self-esteem problems (19)(20)(21), playing multiplayer games (22,23), emotional symptoms (24,25), peer relationship problems (26)(27)(28), family relationship problems (29,30), and male sex (2,12,(31)(32)(33), among others. Therefore, we collected information on these variables, with age and lifestyle factors (which we believe may be related to family support) as candidate predictors.…”
Section: Introductionmentioning
confidence: 93%